Intranasal dexmedetomidine reduces pain scores in preterm infants during retinopathy of prematurity screening - Ozkan Zarif, Nurten; Arayici, Sema; Celik, Kiymet; Kihtir, Zeynep; Ongun, Hakan (Frontiers in Pediatrics, 2024)
Background This study aimed to investigate the effectiveness of intranasal dexmedetomidine in reducing pain scores during retinopathy of prematurity (ROP) screening examinations in preterm infants. Methods Infants born at ≤32 weeks of gestational age, undergoing routine ROP examinations in the neonatal intensive care unit, were included in the study and divided into two groups: the standard protocol group (n = 43) and the dexmedetomidine group (n = 56), over a 1-year period. Both groups received standard procedural preparation including swaddling, oral dextrose, and topical anesthesia with proparacaine. The dexmedetomidine group additionally received intranasal dexmedetomidine at a dose of 1 mcg/kg before the procedure. Pain scores (PIPP score), heart rate, respiratory rate, blood pressure, and oxygen saturation were compared at baseline, 1-min, and 5-min during the procedure. Results There were no significant differences between the groups regarding descriptive and pre-procedure characteristics. In the dexmedetomidine group, the median (25-75p) PIPP score, heart rate, systolic blood pressure and mean (±SD) respiratory rate measured at the 1st minute of the procedure were significantly lower than those in the standard group [PIPP score 10 (8–13) vs. 14 (10–16), p < 0.001; heart rate 165 (153–176) beats/min vs. 182 (17–190) beats/min, p < 0.001; respiratory rate 60 (±7) breaths/min vs. 65(±9) breaths/min, p = 0.002; systolic blood pressure 78 (70–92) mmHg vs. 87 (78–96) mmHg, p = 0.024; respectively] whereas the saturation value was significantly higher (88% (81–95) vs. 84% (70–92), p = 0.036; respectively). By the 5th minute of the procedure, the median (25-75p) PIPP score [4 (2–6) vs. 6 (4–10), p < 0.001], heart rate [148 (143–166) beats/min vs. 162 (152–180) beats/min, p = 0.001] and respiratory rate [56 (54–58) breaths/min vs. 58 (54–62) breaths/min, p = 0.034] were significantly lower, and the saturation level was significantly higher [96% (94–97) vs. 93% (91–96), p = 0.003] in the dexmedetomidine group. Additionally, the frequency of adverse effects was significantly lower in the dexmedetomidine group compared to the standard protocol group (11% vs. 47%, p = 0.001). Conclusion Administering intranasal dexmedetomidine before ROP screening examinations was associated with a decrease in pain scores among preterm infants. This suggests its potential as an effective and well-tolerated method for pain management during ROP screenings.